Comparison of two DNA extraction methods for dry Leaf Dipterocarpaceae - ESSY HARNELLY; NITA TAUHIDA; ISKANDAR ZULKARNAIN SIREGAR (Jurnal Natural, 2022)
DNA extraction is the first step in obtaining high-concentration and high-purity DNA that can use in the subsequent steps. Because the leaf structure is challenging and contains several secondary metabolites that can affect DNA extraction results, DNA extraction on dry leaves of Dipterocarpaceae is considered problematic. This research aims to find a suitable method for extracting DNA from the preserved Dipterocarpaceae leaves. Preserved leaves of Dipterocarpaceae in silica gel will dry up, making them tough to destroy. Perform DNA extraction is generally using CTAB buffers or extraction kits. According to the results of this study, extraction with modified CTAB buffer result in DNA with higher concentration and purity values than DNA extracted with the kit. DNA isolated from the modified CTAB can be used as a template in the PCR process to amplify the matK gene.